School Inputs, Household Substitution, and Test Scores - Das, Jishnu; Dercon, Stefan; Habyarimana, James; Krishnan, Pramila; Muralidharan, Karthik; Sundararaman, Venkatesh (American Economic Association, 2014)
Empirical studies of the relationship between school inputs and test scores typically do not account for household responses to changes in school inputs. Evidence from India and Zambia shows that student test scores are higher when schools receive unanticipated grants, but there is no impact of grants that are anticipated. We show that the most likely mechanism for this result is that households offset their own spending in response to anticipated grants. Our results confirm the importance of optimal household responses and suggest caution when interpreting estimates of school inputs on learning outcomes as parameters of an education production function.